2020
DOI: 10.37256/fse.11202046
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals and Antioxidant Properties of Solvent Extracts from Purslane (Portulaca oleracea L.): A Preliminary Study

Abstract: A systematic study was conducted about the solvent effect on the purslane total phenolic, flavonoid, alkaloid, carotenoid, saponin, vitamin E, and vitamin C contents as well as to evaluate their contribution to overall antioxidant activity. Among three solvents investigated, water could extract the highest levels of solid and saponin contents, whereas methanol was more effective for obtaining phenolic, flavonoid, and alkaloid compounds than other solvents. Meanwhile, ethanol was the best choice for extracting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
0
4
0
4
Order By: Relevance
“…(Liu et al, 2018;Zhang & Tsao, 2016). Considering the importance of polyphenol, in this study, POME has been examined and found to have a high content of polyphenols, which is related to the previous antioxidant-based study (Habibian et al, 2020). In this study, POME was analyzed to contain 2-methoxy-4-vinylphenol, neophytadiene, and friedelan-3-one in GC-MS analysis.…”
mentioning
confidence: 82%
“…(Liu et al, 2018;Zhang & Tsao, 2016). Considering the importance of polyphenol, in this study, POME has been examined and found to have a high content of polyphenols, which is related to the previous antioxidant-based study (Habibian et al, 2020). In this study, POME was analyzed to contain 2-methoxy-4-vinylphenol, neophytadiene, and friedelan-3-one in GC-MS analysis.…”
mentioning
confidence: 82%
“…Several compounds including phenolics, flavonoids, flavonols, and various pigments are reported to exhibit a free radical scavenging activity (Miliauskas et al, 2004;Seyoum et al, 2006;Kumar and Pandey, 2013;Pérez-Gálvez et al, 2020;). In the purslane case, a good correlation between antioxidant activity including free radical scavenging activity with TPC and flavonoids contents was demonstrated by Youssef and Mokhtar (2014), Habibian et al (2020) and Saffaryazdi et al (2020), and A good correlation between DPPH• scavenging activity of purslane and its pigments content (chlorophyll a, chlorophyll b, carotenoids, and β-carotene) was also reported by Habibian et al (2020) and Youssef and Mokhtar (2014). Regarding ferrous iron (Fe +2 ) chelating activity, our findings showed that no significant (p > 0.05) correlation between chelating activity with β-carotene, chlorophyll a, TPC, flavonoids, flavonols, and DPPH scavenging activity.…”
Section: Correlation Analysismentioning
confidence: 93%
“…Los niveles de CFT y antioxidantes están directamente relacionados con procesos de señalización en las plantas, así como defensa contra herbívoros, protección contra el estrés lumínico, tolerancia contra metales pesados y para resguardar el balance redox de las plantas; por lo cual, sus niveles dependerán de las condiciones donde se desarrollen las plantas. Los contenidos detectados en el presente estudio son similares a los reportados por investigaciones anteriores (Santiago-Saenz et al, 2018;Sicari et al, 2018;Habibian et al, 2020) aunque, la identidad química de los agentes responsables de los efectos antioxidantes es desconocida en las accesiones de Tamaulipas.…”
Section: Discusionesunclassified
“…Esta influencia del solvente sobre los niveles y naturaleza de los fitoquímicos extraídos se ha reportado anteriormente en P. oleracea (Habibian et al, 2020), donde además se señala que los contenidos de CFT y los niveles de capacidad colectora contra ABTS y DPPH fueron similares entre extractos etanólicos y acuosos, tal como ocurrió para la mayoría de las accesiones en este estudio. Se ha reportado que los solventes con mayor polaridad permiten la extracción de mayores contenidos de CFT y capacidad colectora de radicales libres, esto explica porque el agua fue más eficiente para extraer estos metabolitos de P. oleracea (Almulaiky et al, 2020).…”
Section: Discusionesunclassified
See 1 more Smart Citation